The illusion of free markets: punishment and the myth of natural order - Harcourt, Bernard E. (Cambridge, Mass., 2012)
"It is widely believed today that the free market is the best mechanism ever invented to efficiently allocate resources in society. Just as fundamental as faith in the free market is the belief that government has a legitimate and competent role in policing and the punishment arena. This curious incendiary combination of free market efficiency and the Big Brother state has become seemingly obvious, but it hinges on the illusion of a supposedly natural order in the economic realm. The Illusion of Free Markets argues that our faith in “free markets” has severely distorted American politics and punishment practices.